Inflation and economic growth: the search for a compromise for the Central Bank's monetary policy - Volodymyr Mishchenko; Svitlana Naumenkova; Svitlana Mishchenko; Viktor Ivanov (Banks and Bank Systems, 2018)
The article analyzes the influence of inflation on economic growth and substantiates the main directions of increasing the effectiveness of the central bank's anti-inflation policy. In order to determine the limit of inflation, the excess of which has a negative impact on the economic growth, the relationship is analyzed between the inflation rate and the real GDP growth rate on the basis of IMF statistics using the example of 158 countries. It was determined that in 2010–2017, in the global economy, the 6.0% inflation was the marginal value of the inflation rate, beyond which the economic growth rate declined or slowed down. Given the inverse relationship between the inflation rate and the real GDP growth rates as well as empirical calculations for the period 1996–2017, the threshold for inflation rate for Ukraine at the level of 4.51% was determined based on empirical calculations for the 1996–2017 period. The results indicate that the National Bank of Ukraine set the inflation target above the level of the calculated threshold inflation. It has also been established that the link between the rates of nominal GDP growth, as opposed to real GDP, and the inflation rate, is more direct and more tight. It is substantiated that to analyze such dependence it is better to use GDP deflator instead of CPI. The results indicate that deflation constrains economic growth much less than inflation. In order to increase the effectiveness of the central bank’s pro-cyclical monetary policy aimed at supporting economic growth, the relationship between the rates of real GDP growth and the indicator characterizing the gap between the growth rates of M3 and inflation, which actually reflects the real money supply dynamics, is determined. The results obtained allowed to conclude that in 2009 and 2014-2017, the artificial “squeezing” of the money supply took place in Ukraine, resulting in a decrease in the level of the economy monetization by 22.0% in 2017 compared to 2013.It has been proved that in order to minimize the negative impact of inflationary processes on economic growth, the policy of the National Bank of Ukraine should be aimed at eliminating the artificial squeezing of the money supply through a reasonable increase in the economy monetization and the implementation of an effective monetary policy.